Aplicación del principio de proporcionalidad según la afectación económica en el delito de peculado - Mafla Sánchez, Johana Lisbeth (2025)
The principle of proportionality in the crime of peculator has presented a significant problem in its way of typification in article 278 of the Comprehensive Organic Criminal Code, which established a penalty of deprivation of liberty in a generalized manner and just considering the distinction of the active subjects, however, this crime does not consider a fundamental aspect such as the economic affectation, even more, when it must be adequate to protect effectively the legal asset protected as well from this type of crime. For this reason, this research established the main objective to carry out a legal analysis regarding the disproportionality in the prison term in the embezzlement crime, but also considering the economic affectation produced to the State to determine the pertinence in a reform of article 278 of the COIP. The methodology used was quantitative, with a non-experimental and transversal design; similarly, surveys were carried out to 50 criminal lawyers in Tulcán, to collect data regarding their perspective of the principle of proportionality in the prison term in the crime of peculator. The results and discussion indicated unanimously that both the surveyed population and the literature reviewed agreed that there exists an inadequate application of the principle of proportionality and therefore supported the pertinence of a legislative reform to article 278 of the COIP, where it should be established a custodial sentence, respecting this principle towards the economic damage caused to the State.